A post occupancy evaluation framework for LEED certified U.S. higher education residence halls. (2015) - Alborz, Nakisa; Berardi, Umberto
Abstract: Numerous higher education (HE) institutions in the United States have created sustainability agendas, including construction of certified sustainable buildings. More than 200 US HE institutions have at least one Leadership in Energy and Environmental Design (LEED) certified building on their campus. In order to assess if sustainable residence buildings are performing as expected, a post occupancy evaluation (POE) framework of indicators was developed and implemented. POE indicators were chosen through a review of sustainability rating systems, literature review, and surveys. The selected indicators address a range of parameters using quantitative and qualitative data collection methods via investigative and diagnostic techniques. The dataset includes temperature and relative humidity measurements, water and energy consumption, feedback from facility manager departments and almost 600 occupants. The findings highlight large variations in terms of energy and water consumption, and poor indoor air quality; moreover, LEED residence halls have also shown to be less sustainable over time. The findings also indicate the LEED rating system may generate skewed savings expectations, as occupant behaviours and feedback are poorly considered.